Advancing sustainable and resilient agriculture in Eastern Nepal's middle hills - International Water Management Institute (International Water Management Institute, 2025)
In Nepal’s middle hills, small landholdings and persistent challenges—such as limited irrigation, transportation, and market access—have long constrained commercial farming and mono-cropping. However, mixed farming systems are proving to be a resilient and sustainable solution for these communities. Through the CGIAR Initiative on Mixed Farming Systems (MFS), IWMI, in collaboration with research and implementation partners, is driving sustainable agricultural intensification in pilot areas. This initiative is helping farmers diversify risks, optimize labour, and enhance productivity—all while safeguarding the environment. Key interventions include promoting efficient water management through micro-irrigation, multiple water use systems, and rainwater harvesting. Additionally, the initiative has strengthened entrepreneurship skills among female and smallholder farmers while fostering stronger networks and collaboration across diverse farming groups. These efforts are making agriculture in Nepal’s hills more sustainable, efficient, and inclusive. With promising results, the initiative holds significant potential for scaling across the region.